A Method for Assessing Leadership Competences - Kral, Zygmunt (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The article proposes a method for assessing the level of leadership competences using a range of assessment criteria. The following research question was adopted: How can the level of leadership competencies be assessed reliably based on the evaluation criteria adopted, and with a synthetic approach (in cross-sections of criteria groups and all criteria jointly)? Leaders’ behaviour was the criterion adopted for assessing the level of leadership competences. Research Design & Methods: Following a presentation of other methods that have been used to assess leadership competences, the multi-criteria method proposed for this paper was based on Roy’s concept of complete aggregation. The method makes it possible to assess the level of leadership competences in the breakdowns included in the research problem. Literature studies and a scientific description were used as general research methods. Findings: The result of the research is a procedure for assessing leadership competences using Roy’s complete aggregation, adapted to the requirements of the adopted research problem. It offers the additional possibility of formalising the assessment of leadership competences. Implications / Recommendations: The results of the research allow us to assume that the proposed procedure makes it possible to assess, in the practice of organisation management, the level of leadership competences in various cross-sections of the criteria for their evaluation. However, the final decisions on the assessment of that level in people, on the basis of the results of the adopted procedure, will be made by humans. Contribution: The author’s proposal contributes to the theory on leadership competences, offers practical guidance on filling leadership positions in an organisation and determining training needs.